High performance lightweight concrete reinforced with glass fibers (Al-Mansour Journal, 2022)
This paper demonstrates the effect of glass fibers on mechanical properties of high performance lightweight concrete which are: compressive strength, flexural strength, workability (flow), and density. Foam agent was used to produce lightweight concreteusing different mix proportion to obtain good workability and compressive strength with least fresh density. Superplasticizer used in some mixes about 1% by weight of cement. Glass fibers were added in different volume fraction 0.06, 0.2, 0.4, and 0.6 %for foam concrete and foam concrete with superplasticizer. The results of foamed concrete mixes indicate that the increase of glass fibers content can produce high performance lightweight concrete and improve the mechanical properties of such concrete. The compressive and flexural strength increased with the increase of glass fibers with acceptable range of workability, addition 0.6% of glass fibers increase 33.7% and 16.1% of compressive and flexural strength respectively but the flow reduced about 38% compare without glass fibers.
Keywords: Lightweight concrete; Foam concrete; Glass fibers; Mechanical properties